On the Practicality of LLM-Based Compiler Fuzzing - Ricardo, Gabriel Guimarães dos Santos; Santos Junior, Natanael dos; Figueiredo, Flavio; Pereira, Fernando Magno Quintão (Anais do Simpósio Brasileiro de Linguagens de Programação (SBLP), 2025)
Recently, Italiano and Cummins introduced an elegant methodology for uncovering performance bugs in compilers. Their approach involves using a pre-trained large language model (LLM) to generate a seed program, followed by successive mutations designed to provoke unexpected behavior, even in mainstream compilers. This methodology uncovered previously unknown (zero-day) performance bugs in widely used compilers such as Clang, ICC, and GCC. In an effort to reproduce the results reported by Italiano and Cummins, we confirm that their technique outperforms general-purpose LLMs, such as open-source versions of LlaMA and DeepSeek, in identifying compiler performance bugs. However, we also observe that while the LLM-based approach is commendable, it lags behind tools like CSmith in terms of throughput (the number of bugs found over time) and latency (the time to discover the first bug). LLMs also require significantly greater computational resources. Although this outcome may seem discouraging, it is important to note that we are comparing novel LLMs with a mature language-specific fuzzer. Nevertheless, as technology evolves, we expect the performance of LLM-based fuzzing to improve, potentially surpassing traditional methods in the future.